CAUSES OF SCHOOL FAILURES DURING STUDIES IN THE OPINION OF TIE STUDENTS FROM THE PEDAGOGICAL UNIVERSITY OF CRACOW - Noga, Henryk; Depešová, Jana; Knych, Aleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
European Union considers school failure as one of the greatest challenges for the education systems in the unifying Europe. What seems to be essential when considering the problem of educational failure is the question of reasons for lack of success in learning performance. This knowledge may help eliminate some factors and find a solution. The research presented in this paper shows the most important factors determining learning failures at collage in the opinion of TIE students of Pedagogical University in Cracow.